ANALISIS PENERAPAN ASPEK AKUNTANSI KEPERILAKUAN TERHADAP KINERJA PEGAWAI PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU PROVINSI NUSA TENGGARA TIMUR - Tiara Heranty Luiza Mooy; Clara Margilina Reinamah (JAKA - Jurnal Jurusan Akuntasi, 2023)
Behavioral accounting considers the relationship between human behavior towards accounting and the information it generates affecting human behavior. Employee factors in behaving in the work environment are required to have good work quality. The phenomenon in the DPMPTSP of NTT Province, as based on the field reality, shows that there are still indications indicating that employee discipline at work is not well implemented, resulting in an impact on employee performance that still shows indications of ineffectiveness in both work quality and time. Based on the above explanation, this research is conducted with the aim of determining the application of behavioral accounting aspects on the performance of employees at DPMPTSP of NTT Province. This research is located at DPMPTSP of NTT Province using a qualitative descriptive method, and data collection is carried out through observation, interviews, and documentation to draw conclusions expected to address the research questions and provide results. The results of the implementation of behavioral accounting at DPMPTSP of NTT Province are quite good based on budgeting and behavior aspects. In terms of the performance of the finance department, everything has been systematic and clearly measured in detail at the Investment and Integrated Service One-Stop Office of NTT Province. The application of behavioral accounting in measuring employee performance plays a good role in creating a conducive work situation and implementing a good and healthy company governance system.